Monitoring COVID-19 Impacts on Households in Vietnam, Report No. 1 : Results Snapshot from a High-Frequency Phone Survey of Households - Yang, Judy; Panagoulias, Philomena; Demarchi, Giorgia (World Bank, Washington, DC, 2020)
Coronavirus (COVID-19) has significantly affected many economies throughout the world, but there are some brighter signs in Vietnam. To monitor the social and economic effects on households amid the pandemic, the World Bank designed and conducted its Coronavirus (COVID-19) high-frequency phone surveys of households in Vietnam. This monitoring data helps gather insights on household well-being as post-lockdown reopening unfolds, and to highlight the effects on the most vulnerable members of Vietnamese society. The first round of the Vietnam household high-frequency phone survey was conducted between June 5 to July 8, 2020. Over six thousand households were contacted from all provinces in the country. This note provides a snapshot of results from the first of four rounds of high frequency surveys.